Associations between three specific a-cellular measures of the oxidative potential of particulate matter and markers of acute airway and nasal inflammation in healthy volunteers. Issue 1 (7th August 2014) - Janssen, Nicole A H; Strak, Maciej; Yang, Aileen; Hellack, Bryan; Kelly, Frank J; Kuhlbusch, Thomas A J; Harrison, Roy M; Brunekreef, Bert; Cassee, Flemming R; Steenhof, Maaike; Hoek, Gerard
Abstract : Introduction: We evaluated associations between three a-cellular measures of the oxidative potential (OP) of particulate matter (PM) and acute health effects. Methods: We exposed 31 volunteers for 5 h to ambient air pollution at five locations: an underground train station, two traffic sites, a farm and an urban background site. Each volunteer visited at least three sites. We conducted health measurements before exposure, 2 h after exposure and the next morning. We measured air pollution on site and characterised the OP of PM2.5 and PM10 using three a-cellular assays; dithiotreitol (OP DTT ), electron spin resonance (OP ESR ) and ascorbic acid depletion (OP AA ). Results: In single-pollutant models, all measures of OP were significantly associated with increases in fractional exhaled nitric oxide and increases in interleukin-6 in nasal lavage 2 h after exposure. These OP associations remained significant after adjustment for co-pollutants when only the four outdoor sites were included, but lost significance when measurements at the underground site were included. Other health end points including lung function and vascular inflammatory and coagulation parameters in blood were not consistently associated with OP. Conclusions: We found significant associations between three a-cellular measures of OP of PM and markers of airway and nasal inflammation. However, consistency of these effects in two-pollutant models depended on how measurements at the underground site were considered. Lung function and vascular inflammatory and coagulation parameters in blood were not consistently associated with OP. Our study, therefore, provides limited support for a role of OP in predicting acute health effects of PM in healthy young adults.